2014
DOI: 10.1002/cbin.10236
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin promotes cardiac microvascular endothelial cells proliferation, migration and survival by phosphorylation of p70 S6K and FoxO3a

Abstract: Restenosis severely limits the overall efficacy of interventions. One of the reasons is the lack of reendothelialization related to inhibition of endothelial cell proliferation and migration since drug is delivered to the luminal surface. Statins can promote angiogenic processes by improving endothelial function, proliferation and migration in cardiac microvascular endothelial cells (CMECs). This study clarified the effect of simvastatin on Akt/mTOR/p70 S6K and FoxO3a signalling pathways in rat CMECs following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…One study has found that mTOR plays crucial role in the normal spermatogenesis process and can preferentially regulate p70s6k rather than 4e-bp1 to promote cell proliferation [12,38,39]. Simvastatin has been shown to induce proliferation, migration and reduce apoptosis of endothelil cells via mTOR signaling pathways [40]. We hypothesized that fluvastatin may act through similar mechanisms on spermatogonia in our model.…”
Section: Discussionmentioning
confidence: 89%
“…One study has found that mTOR plays crucial role in the normal spermatogenesis process and can preferentially regulate p70s6k rather than 4e-bp1 to promote cell proliferation [12,38,39]. Simvastatin has been shown to induce proliferation, migration and reduce apoptosis of endothelil cells via mTOR signaling pathways [40]. We hypothesized that fluvastatin may act through similar mechanisms on spermatogonia in our model.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, nerenone appears to provide favorable vascular effects through restoring vascular integrity and preventing adverse vascular remodeling [32]. Besides, low dosage of simvastatin can induce cardiac microvascular ECs proliferation, migration and anti-apoptosis via PI3K/Akt/mTOR/p70S6K and mTOR/FoxO3 signalling pathways, and then exert a bene cial effect by regulation of NO and ROS production in microvascular ECs [33]. In our research, we also con rmed that iron evidently aggravated ECs injury via aggravating lysosomal injury and LAP could alleviate ECs injury triggered by redox-active iron decomposed by OxyHb.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signal pathway is considered a key regulator of cell growth, proliferation, and cell cycle progression. Phosphorylation of AKT/mTOR/P70S6K prevents dysfunction and apoptosis of cardiac microvascular endothelial cells . In many cancers, the abnormal activation of the AKT/mTOR signal prevents cells from undergoing apoptosis and maintains cell growth .…”
Section: Discussionmentioning
confidence: 99%